Molecular Neurosurgery: Introduction to Gene Therapy and Clinical Applications - Addison, Angela P.; McGinnis, J.P.; Ortiz-Guzman, Joshua; Tantry, Evelyne K.; Patel, Dhruv M.; Belfort, Benjamin D. W.; Srivastava, Snigdha; Romero, Juan M.; Arenkiel, Benjamin R.; Curry, Daniel J. (Journal of Pediatric Epilepsy, 2023)
To date, more than 100 clinical trials have used sequence-based therapies to address diseases of the pediatric central nervous system. The first targeted pathologies share common features: the diseases are severe; they are due (mostly) to single variants; the variants are well characterized within the genome; and the interventions are technically feasible. Interventions range from intramuscular and intravenous injection to intrathecal and intraparenchymal infusions. Whether the therapeutic sequence consists of RNA or DNA, and whether the sequence is delivered via simple oligonucleotide, nanoparticle, or viral vector depends on the disease and the involved cell type(s) of the nervous system. While only one active trial targets an epilepsy disorder—Dravet syndrome—experiences with aromatic L-amino acid decarboxylase deficiency, spinal muscular atrophy, and others have taught us several lessons that will undoubtedly apply to the future of gene therapy for epilepsies. Epilepsies, with their diverse underlying mechanisms, will have unique aspects that may influence gene therapy strategies, such as targeting the epileptic zone or nodes in affected circuits, or alternatively finding ways to target nearly every neuron in the brain. This article focuses on the current state of gene therapy and includes its history and premise, the strategy and delivery vehicles most commonly used, and details viral vectors, current trials, and considerations for the future of pediatric intracranial gene therapy.
Keywords: molecular neurosurgery; gene therapy; epileptic; epilepsy